Elevated BP180 ELISA at Diagnosis Correlates with Disease Severity and Relapse in Oral Mucous Membrane Pemphigoid: Preliminary Results from a Retrospective Monocentric Italian Study - Andrea Gabusi; Davide B. Gissi; Roberto Rossi; Federica Filippi; Camilla Loi; Cosimo Misciali; Giacomo Clarizio; Michelangelo La Placa; Federico Bardazzi (Applied Sciences)
Background: Little is known about the relevance of BP180 ELISA for the clinical management of oral mucous membrane pemphigoid (OMMP). The aim of the present study was to investigate if the levels of anti-BP180 antibodies at diagnosis could be correlated with clinical severity and relapse. Methods: The present study included 44 OMMP patients with positive direct immunofluorescence (DIF). Circulating anti-BP180 IgG was measured using the same available ELISA kit (Euroimmun cut-off 20 U/mL). Clinical severity at diagnosis was measured using the oral disease severity score (ODSS). Only patients who achieved clinical remission (CR) were included in the analysis of variables related to relapse. Relapse was calculated as the interval between the date of the best type of clinical remission achieved and the date of relapse. Results: Values of BP180 > 20 U/mL significantly correlated with higher ODSSs in both univariate (p < 0.05) and multivariate analyses (p < 0.05). Among 39/44 patients who achieved CR, 17/39 relapsed. Kaplan–Meier analysis revealed that patients with BP180 > 20 U/mL displayed worse clinical behavior in terms of relapse (p < 0.05). Conclusion: BP180 ELISA at diagnosis appears to be a useful parameter to stratify OMMP patients with more severe disease and worse clinical outcomes after clinical remission.